If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 9 = 2(7x + -6) Reorder the terms: 9 + 8x = 2(7x + -6) Reorder the terms: 9 + 8x = 2(-6 + 7x) 9 + 8x = (-6 * 2 + 7x * 2) 9 + 8x = (-12 + 14x) Solving 9 + 8x = -12 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 9 + 8x + -14x = -12 + 14x + -14x Combine like terms: 8x + -14x = -6x 9 + -6x = -12 + 14x + -14x Combine like terms: 14x + -14x = 0 9 + -6x = -12 + 0 9 + -6x = -12 Add '-9' to each side of the equation. 9 + -9 + -6x = -12 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = -12 + -9 -6x = -12 + -9 Combine like terms: -12 + -9 = -21 -6x = -21 Divide each side by '-6'. x = 3.5 Simplifying x = 3.5
| 13*4-22/11+5*x=75 | | 40+3x=-20 | | (3+w)w+w+(3+w)=24 | | 2x-5=34+x | | 7(c-9)=9(2c-8)+4 | | iman=5 | | 3x^2-6x-5=4 | | 12-5u= | | 3x^4-4x^2-1=0 | | lg(2x+40)=1.75 | | 8x+3(20-x)=125 | | 57.50-8=49.50 | | a+1/2=1 | | 731848618382638+7782658236472634972347692= | | 2(x-1)+10x=5(2x+3)+4 | | factorx^2-3x+1=0 | | x^2+2*(k-3)*x+(k-1)=0 | | 4(2x+5)+9v=36 | | 4x-8-2x=2(x-4) | | ax+b=2x | | A+3=b | | 7x+4=-x+-10 | | k+3.91=287 | | 4Y-8=3Y-4 | | 5x^4-3x^2=0 | | 22-7=3a | | 12.45=g+4g | | 1.21=5z+6z | | -61-7=17 | | 125=13c+12c | | 6x+9=-9+8x | | 5x+37=8x-8 |